Association of Adiponectin Level and Type 2 Diabetes Mellitus (T2DM): A Systematic Review and Meta-Analysis - Nathan, Daniel Setiawan; Yumilia, Hoo (International Journal For Research In Health Sciences And Nursing, 2022)
Experimental and epidemiologic evidence has accumulated that supports a beneficial role of adiponectin, a major cytokine secreted from adipocyte, in glucose metabolism. Mechanistic studies show that adiponectin improves insulin sensitivity and inflammation, important mechanisms in the development of type 2 diabetes. Method: This study is a systematic review and meta-analysis conducted to see the relationship between adiponectin levels and the incidence of type 2 diabetes mellitus. The research involved in this review was taken from journal databases, such as: Pubmed, Google Scholar, and Sage Pub. The included studies were studies involving both diabetic and non-diabetic humans, the study clearly showed blood sugar levels and adiponectin levels of the study sample. Result: Researchers included 7 reviewed studies for analysis discussing adiponectin as a risk factor for type 2 DM and related complications. Conclusion: There is an inverse relationship between adiponectin levels and the incidence of diabetes and associated vascular complications.